A new species of the Bokermannohyla pseudopseudis group from central Bahia, Brazil (Amphibia, Hylidae) - Lugli, Luciana [UNESP]; Haddad, Célio F. B. [UNESP] (Herpetologists League, 2006)
A new species of treefrog is described from Chapada Diamantina in the central State of Bahia, Brazil. The new species is a member of the Bokermannohyla pseudopseudis group, characterized by its small to medium size, head as long as wide, snout short, rounded in dorsal view and nearly truncate in lateral view, eyes and tympanum large, and forearm and prepollex well developed. The new species can be distinguished from the other species of the B. pseudopseudis group by its voice and the shape of its head and snout. It is smaller than B. saxicola and B. pseudopseudis, and has a less developed forearm and prepollex than B. ibitiguara males. The tadpole and vocalizations are described and information on natural history is provided. © 2006 by The Herpetologists' League, Inc.
Keywords: Bokermannohyla; Chapada Diamantina - Bahia; New species